Bahasa Positif Sebagai Sarana Pengembangan Pendidikan Moral Anak - Siti Saudah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
Moral degradation is getting widerspread in Indonesia. Polite, friendly, and religious manners have been displaced as the effects of modern lifestyle. Hence, moral values is very important to be developed from the early ages. This paper is an outlook to address moral education on children based on research. The research methods used are observation, mentoring and questionnaire. Data analysis is conducted by describing the results of observation during the mentoring and calculating the results of questionnaire with spss 15.0. Mentoring is conducted by building the habit of using positive language in class through 4 skills: listening, speaking, reading and writing. The development of moral education of the students can be seen from the results of the questionnaire: pre-test conducted before mentoring and post test conducted after mentoring. The researh result shows that pre-test featured 46 % and post-test was 54%. It means that there is an increase of 8 % on mentoring. Therefore, it can be concluded that positive language that often used or listened by the students will influence their ways of thinking that finally will build the students’ character.